Free-floating left atrial thrombi with acquired protein C deficiency in hepatitis - Sabzi Feridoun; Faraji Reza; Heydarizadeh Hedayat (Sciendo, 2023)
A 43-year-old woman with a recent history of confirmed hepatitis B presented with yellow sclera and dyspnea. Clinically, she had tachycardia and tachypnea as well as signs of jaundice and right upper quadrant pain. She was in sinus rhythm with a normal aspect of cardiac examination. She was treated with corticosteroids and her symptoms were partially relieved, however, her mild fever remained unchanged and a transthoracic echocardiogram (TTE) and transesophageal echocardiography (TEE) were done to rule out embolic or in situ infective endocarditis. Images from the TEE and TTE showed a ping-pong-like clot in the left atrium with a normal cardiac function and a normal mitral valve function. The mitral leaflets appeared to be normal with no regurgitation, and no clot was noted in other chambers or valves, including the atrial appendages. A differential diagnosis of infective vegetations, clots, or tumors was considered. The three subsequent blood cultures were negative. A complete thrombophilia assay revealed a severe reduced protein C factor, however, the IgG anti cardiolipin and lupus anticoagulant were normal. The woman's anti-nuclear antibody and anti-double-stranded DNA were negative, confirming the diagnosis of acquired protein C deficiency. The patient underwent an open surgical removal of the clot and postoperative treatment with steroids, warfarin, and heparin. The postoperative course was uneventful, and the patient was discharged on the 13th day of operation in good condition. This case was interesting because we did not find any mitral valve pathology such as mitral stenosis, or arrhythmia like atrial fibrillation.